Breast cancer risk in relation to ambient concentrations of nitrogen dioxide and particulate matter: results of a population-based case-control study corrected for potential selection bias (the CECILE study). (October 2021) - Lemarchand, Clémentine; Gabet, Stephan; Cénée, Sylvie; Tvardik, Nastassia; Slama, Rémy; Guénel, Pascal
Highlights: Exposure to NO2 was associated with increased breast cancer risk. This association was stronger for hormone receptor-positive breast tumors. Reducing traffic-related air pollution could prevent a significant number of cases. Abstract: Background: There is only scant evidence that air pollution increases the risk of breast cancer. Objectives: We investigated this relationship for three air pollutants: nitrogen dioxide (NO2 ) and particulate matter with an aerodynamical diameter below 10 µm (PM10 ) and 2.5 µm (PM2.5 ). Methods: We conducted a population-based case-control study on breast cancer in two French départements, including 1, 229 women diagnosed with breast cancer in 2005–2007 and 1, 316 control women frequency-matched on age. Concentrations of NO2, PM10 and PM2.5 at participants' addresses occupied during the last 10 years were assessed using a chemistry transport model. Odds ratios (OR) and 95% confidence intervals (95% CI) were estimated using multivariable logistic regression models where each woman was assigned a weight depending on her probability of selection into the study. Results: The OR for breast cancer per 10-µg/m 3 increase in NO2 was 1.11 (95% CI, 0.98, 1.26), and 1.41 (95% CI 1.07, 1.86) in the highest exposure quintile (Q5), compared to the first. The ORs per 10-µg/m 3 NO2 did not markedly differ between pre- (OR 1.09, 95% CI 0.89, 1.35)) and post-menopausal women (OR 1.14, 95% CI 0.97, 1.33)), but the OR was substantially higher for hormone-receptor positive (ER+/PR+) breast tumor subtypes (OR 1.15, 95% CI 1.00, 1.31) than for ER–/PR– tumors (OR 0.95, 95% CI 0.72, 1.26). Breast cancer risk was not associated with either PM10 (OR per 1 µg/m 3 1.01, 95% CI, 0.96, 1.06) or PM2.5 (OR per 1 µg/m 3 1.02, 95% CI 0.95, 1.08), regardless of the menopausal status or of the breast tumor subtype. Discussion: Our study provides evidence that NO2 exposure, a marker of traffic-related air pollutants, may be associated with an increased risk of breast cancer, particularly ER+/PR+ tumors.